Human papilloma virus load and PD-1/PD-L1, CD8+ and FOXP3 in anal cancer patients treated with chemoradiotherapy: Rationale for immunotherapy. (4th March 2017) - Balermpas, Panagiotis; Martin, Daniel; Wieland, Ulrike; Rave-Fränk, Margret; Strebhardt, Klaus; Rödel, Claus; Fokas, Emmanouil; Rödel, Franz
ABSTRACT: We examined the prognostic role of immune markers programmed cell death protein-1 (PD-1) and its ligand (PD-L1), CD8 + tumor-infiltrating lymphocytes (TILs), FOXP3+ Tregs and phosphorylated Caspase-8 (T273) in patients with anal squamous cell cancer (ASCC) treated with standard chemoradiotherapy (CRT). The baseline immunohistochemical expression of immune markers was correlated with clinicopathologic characteristics, and cumulative incidence of local failure, disease-free survival (DFS) and overall survival (OS) in 150 patients, also in the context of human papilloma virus 16 (HPV16) DNA load and p16 INK4a expression. After a median follow-up of 40 mo (1–205 mo), the 5-y cumulative incidence of local failure and DFS was 19.4% and 67.2%, respectively. Strong immune marker expression was significantly more common in tumors with high HPV16 viral load. In multivariant analysis, high CD8 + and PD-1+ TILs expression predicted for improved local control ( p = 0.023 and p = 0.007, respectively) and DFS ( p = 0.020 and p = 0.014, respectively). Also, high p16 INK4a ( p = 0.011) and PD-L1 ( p = 0.033) expression predicted for better local control, whereas high FOXP3+ Tregs ( p = 0.050) and phosphorylated Caspase-8 ( p = 0.031) expression correlated with superior DFS. Female sex and high HPV16 viral load correlated with favorable outcome for all three clinical endpoints. The present data provide, for the first time, robust explanation for the favorable clinical outcome of HPV16-positive ASCC patients harboring strong immune cell infiltration. Our findings are relevant for treatment stratification with immune PD-1/PD-L1 checkpoint inhibitors to complement CRT and should be explored in a clinical trial.